(Paleo)glacier studies in Patagonia over the past decades (1976-2020): A bibliometric perspective based on the Web of Science - Soteres, Rodrigo L.; Riquelme, Fabian M.; Sagredo, Esteban A.; Kaplan, Michael R. (My University, 2023)
Patagonia features the most extensive glaciers of the Southern Hemisphere, excluding Antarctica, and a vast inventory of glacial landforms, so it is thought to have played a key role in (paleo)glacier studies since the late 19th century. However, no systematic attempts to characterize the specific research trends and the scientific community focused on Patagonian cryosphere have been conducted so far. To fill this gap, we analyzed the metadata associated to 305 articles compiled from the Web of Science database following a bibliometric approach covering the period between 1976 and 2020. Our results point to an irregular but net increase on the number of contributions on Patagonian (paleo)glaciers. Mass balance analyses based on satellite data of presentday glaciers and the reconstruction of past glacier activity by dating glacial landforms formed during the Last Glacial Termination, were the most addressed topics during the analyzed period. Patagonian (paleo)glacier studies are mostly published in generic Earth Sciences publications, followed by Quaternary and glaciological journals. Most of the studies were led by scientists from the United Kingdom, followed by Chile, Argentina and United States. In terms of collaborations, these studies can be divided into two main clusters, one composed by researchers from United States, Chile and Argentina institutions, and another mostly composed by British researchers. So far, the most prolific authors are nearly equally distributed in nationality, yet gender inclusion and international collaborations are still caveats that must be solved. Even though our query on the Web of Science missed highly influential (so-called) grey literature, such as local scientific journals and technical reports, the reviewed scientific literature unambiguously indicates that Patagonia is a privileged location for (paleo)glaciers studies worldwide and that it will continue offering vast opportunities to tackle critical questions related to global cryosphere and past-to-present climate changes.
Keywords: last glacial maximum; last glacial termination; holocene; 20th century; patagonia; glaciers